The Influence of Organizational Climate on Simultaneous the Effectiveness of General Election Public Services During the Covid-19 Pandemic - Rahmat Ismail Datau; Lisda Van Gobel; Elnino Husain Mohi (Program Pascasarjana Universitas Negeri Makassar, 2022)
ABSTRACTThis research aims to determine and analyze the influence of organizational climate on simultaneous general election public services during the Covid-19 Pandemic at the General Election Commission Bone Bolango regency. This study uses a questionnaire as a primary data collection tool and data analysis techniques in quantitative research using statistics. The statistical test used in this study is descriptive statistics which is carried out to find the effect between the two variables through analysis of the regression test. The variables used in this study are Organizational Climate as the independent variable and public service as the dependent variable. This study found that the simple linear regression coefficients from organizational climate data and the effectiveness of simultaneous general election public services during the Covid-19 Pandemic were obtained at a = 19.38 and b = 0.30. Thus, the form of the simple linear regression equation obtained is Y = 19.38 + 0.30x. The results of the analysis of variance show that this equation is linear. In other words, the linear regression equation model is accepted and can be used to predict that if the organizational climate increases by one unit, the effectiveness of simultaneous general election public services during the Covid-19 Pandemic will increase by 0.30 units at a constant rate of 19.38 .